(untitled) (Research, Society and Development, 2023)
Biotechnology is increasingly present in everyday life and offers various possibilities of application in our lives. It is imperative to understand how it is being addressed in Science Education. The present work seeks to understand the scope involving research on Biotechnology presented at the National Meeting for Research in Science Teaching (ENPEC), reviewing since its first edition in 1997, a total of 11 editions of the event. For the survey, the word Biotechnology was considered, understanding its complexity and the processual inherent to it. We defend the approach of the modes of transition, intervocalic and intermediary, having the cartography as a rhizomatic perspective and the possibility of a methodological operator. The publications were explored through lines that permeated the titles, keywords, and abstracts, in order to follow the flow of papers published in ENPEC that relate to the theme of Biotechnology. We organized our map of information by year of publications; post graduation programs are researching/writing on the theme and authorship. We verified with concern that the theme is incipient in the area, having a reduced number of 10 works that approached biotechnology. Thus, we argue that further research is needed to investigate and disseminate its possibilities to discuss scientific uncertainties and interdisciplinarity in Science Teaching.